2012
DOI: 10.1038/ismej.2012.67
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity in relation to secondary production and succession on surfaces of the kelp Laminaria hyperborea

Abstract: Kelp forests worldwide are known as hotspots for macroscopic biodiversity and primary production, yet very little is known about the biodiversity and roles of microorganisms in these ecosystems. Secondary production by heterotrophic bacteria associated to kelp is important in the food web as a link between kelp primary production and kelp forest consumers. The aim of this study was to investigate the relationship between bacterial diversity and two important processes in this ecosystem; bacterial secondary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 51 publications
7
116
2
Order By: Relevance
“…This is consistent with previous findings on the bacterial community associated in January 2007 with another Fucales species, Fucus vesiculosus, as this bacterial community appeared to be dominated by Alphaproteobacteria and Gammaproteobacteria species (20). Nonetheless, Bacteroidetes and Planctomycetes species are also relatively abundant on brown algal surfaces (20,43), and one might be surprised that our functional metagenomic screen yielded no loci identified as originating from these phyla. An explanation might be that our E. coli expression strain (Gammaproteobacteria) does not readily recognize gene promoters of Bacteroidetes and Planctomycetes species.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous findings on the bacterial community associated in January 2007 with another Fucales species, Fucus vesiculosus, as this bacterial community appeared to be dominated by Alphaproteobacteria and Gammaproteobacteria species (20). Nonetheless, Bacteroidetes and Planctomycetes species are also relatively abundant on brown algal surfaces (20,43), and one might be surprised that our functional metagenomic screen yielded no loci identified as originating from these phyla. An explanation might be that our E. coli expression strain (Gammaproteobacteria) does not readily recognize gene promoters of Bacteroidetes and Planctomycetes species.…”
Section: Discussionsupporting
confidence: 92%
“…Pairwise comparisons revealed that T. prototypum samples had significantly higher estimated species richness (1026.58 ± 610.00 OTUs) compared with H. boergesenii (196.08 ± 74.96 OTUs, Dunn's Method, Po0.05, Figure 2). Bacterial species richness increases with algal age for some algal species (Bengtsson et al, 2012). The high level of species richness found on the surface of T. prototypum may be related to the fact that this CCA species, unlike the others tested here, does not slough its surface cells (see supplementary material in Ritson-Williams et al, 2014) allowing for the development of a more mature bacterial community.…”
Section: Interspecies Variability: Diversitymentioning
confidence: 71%
“…Although macroalgae and seagrasses form habitats worldwide known as hotspots of biodiversity and production, we know little about the microbes in these ecosystems (Bengtsson et al, 2012), but see Clasen and Shurin (2015) for an ecosystem approach. The relative few microbial studies performed have focused almost exclusively on (epi-)bacterial communities associated to seagrasses and macroalgae, neglecting most other microbes (Bengtsson et al, 2012;Bockelmann et al, 2012Bockelmann et al, , 2013Michelou et al, 2013;Brakel et al, 2014Brakel et al, , 2017Cúcio et al, 2016;Singh and Reddy, 2016). On top of that, particularly functional interactions between marine macrophytes and their microbiomes are poorly known.…”
Section: A3 Marine Macrophyte Holobionts and Their Hologenomesmentioning
confidence: 99%